The impact of incentives on prosocial behavior: An experimental investigation with German and Chinese subjects - Guanzhong Yang (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
Economists believe in (monetary) incentives. However, in the specialized area of prosocial behaviours, (monetary) incentives could backfire because extrinsic motivation might crowd out intrinsic motivation. Moreover, national differences in the perception of incentives should also be considered, taking the cultural background of individuals into account. In this project, we ran a real effort experiment in Germany and in China. In addition to an extrinsic monetary incentive (personal payment) to the subjects, we made a donation to UNICEF, and the amount of the donation depended on the effort of the subjects, which served as an intrinsic motivation. The results indicate that with respect to activities with a prosocial element, Germans tended to exert a high level of effort, regardless of the alternation of the art and the level of their payoff; in contrast, the Chinese did react to extrinsic monetary incentives and exerted more effort with a linear payment or if the level of payment was high. Females exerted significantly more effort than males, and this was true for both the German and Chinese subjects. The last finding is that the Chinese were more motivated by a fixed non-monetary payment than a fixed monetary payment, if the level of payment was relatively low.
Keywords: C91; D64; L31; 330; monetary incentives; prosocial behaviour; intrinsic and extrinsic motivation